The Role of 5-Phosphodiesterase Inhibitors (PDE-5I) in Current Benign Prostatic Hyperplasia Treatment: A Narrative Review - Konstantinos Stamatiou; Gianpaolo Perletti; Vittorio Magri; Alberto Trinchieri (Medicina)
Introduction: 5-phosphodiesterase inhibitors (PDE-5I) have been investigated as a treatment for urinary dysfunction for almost a decade. The general perception is that they play a significant role in managing lower urinary tract symptoms (LUTS), particularly those associated with benign prostatic hyperplasia (BPH). However, the specific biochemical processes by which PDE-5I repairs urinary function are still poorly understood and there is little instrumental evidence of significant improvement in urinary symptoms. Therefore, we explore the role of 5-phosphodiesterase inhibitors (PDE-5I) as complementary to the conventional treatment of symptomatic BPH; we provide the suggested biological procedures involved in the association between PDE-5 inhibitor use and improvement in LUTS; and we propose new approaches to this topic. Material and Methods: A systematic search for clinical trials, experimental studies, and systematic reviews was performed in electronic libraries (PubMed, EMBASE, Scopus) using the terms “benign prostate hypertrophy”, “benign prostate hyperplasia”, “lower urinary tract symptoms”, “storage symptoms”, “voiding symptoms”, “bladder outlet obstruction” and the keywords “mechanism of action”, “synergy”, “PDE-5 inhibitor”, “alpha1-adrenergic antagonist”, “5-alpha-reductase inhibitors” in various combinations. There was no restriction on publication date. Results: To date, only a few randomized studies have been published in which the effect of the combination of a conventional drug for the treatment of symptomatic BPH and a PDE-5I was investigated. Almost all showed significant improvement in IPSS and QoL. Some studies showed significant improvements in maximum urine flow (Qmax) and postvoiding residual volume (PVR) with combination therapy compared with a single agent alone. Conclusions: PDE-5I seems effective in relieving symptoms of some BPH patients when administered as complementary to agents currently used to treat BPH. However, the mechanism of action of PDE-5 inhibitors in LUTS remains poorly understood and it is difficult to determine the specific subset of BPH patients who will benefit from the combination of PDE-5 inhibitors with the current treatment. Well-designed, sufficiently informative comparative studies focusing on specific target group profiles (age, urogenital parameters) are needed to define new therapeutic options.